2017
DOI: 10.1016/j.celrep.2017.08.072
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Quaternary Organization Explains G Protein-Coupled Receptor Family Structure

Abstract: SummaryThe organization of Rhodopsin-family G protein-coupled receptors (GPCRs) at the cell surface is controversial. Support both for and against the existence of dimers has been obtained in studies of mostly individual receptors. Here, we use a large-scale comparative study to examine the stoichiometric signatures of 60 receptors expressed by a single human cell line. Using bioluminescence resonance energy transfer- and single-molecule microscopy-based assays, we found that a relatively small fraction of Rho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 57 publications
5
55
0
Order By: Relevance
“…The use of BRET‐ and single‐molecule microscopy‐based assays on several members of the rhodopsin family of GPCR recently showed that a relatively small fraction of these receptors behave as dimers, while the major proportion appears to be monomeric . In this analysis, CXCR4 was included in a subgroup of dimer‐forming GPCR whereas closely related CKR such as CCR6 or CCR1 were not.…”
Section: Chemokine Receptors: Additional Levels Of Complexitymentioning
confidence: 90%
See 2 more Smart Citations
“…The use of BRET‐ and single‐molecule microscopy‐based assays on several members of the rhodopsin family of GPCR recently showed that a relatively small fraction of these receptors behave as dimers, while the major proportion appears to be monomeric . In this analysis, CXCR4 was included in a subgroup of dimer‐forming GPCR whereas closely related CKR such as CCR6 or CCR1 were not.…”
Section: Chemokine Receptors: Additional Levels Of Complexitymentioning
confidence: 90%
“…57 The use of BRET-and single-molecule microscopy-based assays on several members of the rhodopsin family of GPCR recently showed that a relatively small fraction of these receptors behave as dimers, while the major proportion appears to be monomeric. 58 In this analysis, CXCR4 was included in a subgroup of dimer-forming GPCR whereas closely related CKR such as CCR6 or CCR1 were not. This study was performed in the absence of ligands, that is, under steady-state conditions, therefore, possible ligand-mediated clustering effects were not considered.…”
Section: Chemokine Receptors: Additional Levels Of Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…If the RLuc8 donor fusion molecule catalyzed the coelenterazine 400a and the GFP 2 acceptor fusion molecule is located less than 10 nm from the donor, a transfer of energy will occur from the donor to the acceptor. This method has been widely used to study PPI (Bery et al., ; Felce et al., ; Mercier et al., ) and also PPI inhibition by small molecules (Beautrait et al., ; Corbel et al., ; Corbel et al., ; Lavoie et al., ; Mazars & Fahraeus, ; Quevedo et al., ) or macromolecules (Bery et al., ; Guillard et al., ; Spencer‐Smith et al., ). It offers several advantages: it is a very sensitive technique as it is based on luminescence, there is no background signal from cellular autofluorescence.…”
Section: Commentarymentioning
confidence: 99%
“…The bivalent ligand AP20187 is a crosslinker that enables ligand-dependent ''dimerization'' of two membrane proteins fused to mutant FKBP domains. FKBP-mediated crosslinks have also been used as positive controls for ''dimerization'' in type 1 and 3 BRET experiments with one protein fused to FKBP and GFP 2 and the other protein fused to FKBP and Rluc (6). However, in the clever type 4 experiment for heterodimers, the GFP 2 -and Rluc-fusion constructs are generated for receptor A, and the FKBP-or (FKBP) 3 -fusion constructs are generated for receptor B.…”
mentioning
confidence: 99%